Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Pada Badan Kesatuan Bangsa Dan Politik Provinsi Lampung - Irawan, Riki; Selamat, Selamat (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Transformational leadership is recognized for its ability to inspire and motivate team members to reach their maximum potential, while work motivation encompasses various internal and external factors that drive employees to excel. This study employs a quantitative approach with a survey method to collect data from employees of the Kesbangpol. The data is analyzed using multiple linear regression to determine the extent to which transformational leadership and work motivation affect employee performance. The findings reveal that transformational leadership significantly impacts the enhancement of employee performance, while work motivation also positively contributes to performance. The study suggests that implementing transformational leadership styles and effective motivation strategies can improve organizational performance, particularly in government agencies like Kesbangpol. The objective of this research is to examine the influence of transformational leadership and work motivation on employee performance. The hypothesis posits that transformational leadership and work motivation have both partial and simultaneous effects on employee performance. The sample comprises 46 respondents. Data collection techniques include observation, documentation, and questionnaires. Data analysis is conducted using a quantitative approach with SPSS version 21.0, encompassing validity testing, reliability testing, simple and multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests. The hypothesis testing results indicate that transformational leadership has a positive partial effect on employee performance with a contribution of 49.9%. Work motivation positively impacts employee performance with a contribution of 38.8%. The combined effect of leadership and work motivation on employee performance is 52,8%.